Recent im/migration to Canada linked to unmet health needs among sex workers in Vancouver, Canada: Findings of a longitudinal study. Issue 5 (4th May 2017) - Sou, Julie; Goldenberg, Shira M.; Duff, Putu; Nguyen, Paul; Shoveller, Jean; Shannon, Kate
ABSTRACT: Despite universal health care in Canada, sex workers (SWs) and im/migrants experience suboptimal health care access. In this analysis, we examined the correlates of unmet health needs among SWs in Metro Vancouver over time. Data from a longitudinal cohort of women SWs (An Evaluation of Sex Workers Health Access [AESHA]) were used. Of 742 SWs, 25.5% reported unmet health needs at least once over the 4-year study period. In multivariable logistic regression using generalized estimating equations, recent im/migration had the strongest impact on unmet health needs; long-term im/migration, policing, and trauma were also important determinants. Legal and social supports to promote im/migrant SWs' access to health care are recommended.